115k views
4 votes
Factor completely6x2+8x+2. Fill in the blanks using the correct sign: 2(3x+ )(x+ )

User MashukKhan
by
4.5k points

2 Answers

6 votes

Answer:

2(3x + 1)(x + 1)

Explanation:

Given

6x² + 8x + 2 ← factor out 2 from each term

= 2(3x² + 4x + 1) ← factor the quadratic

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term

product = 3 × 1 = 3 and sum = 4

The factors are + 3 and + 1

Use these factors to split the x- term

3x² + 3x + x + 1 ( factor the first/second and third/fourth terms )

= 3x(x + 1) + 1(x + 1) ← factor out (x + 1) from each term

= (3x + 1)(x + 1) , then

3x² + 4x + 1 = (3x + 1)(x + 1)

and

6x² + 8x + 2 = 2(3x + 1)(x + 1) ← in factored form

User VzR
by
4.5k points
5 votes

Answer:

2(3x+1)(x+1)

Explanation:

First, we factor out the common term, which is 2.

2(3x²+4x+1)

Then, we factor the polynomial inside the parenthesis.

2(3x+1)(x+1)

User Beaux
by
4.9k points